P76 Impact of the COVID-19 pandemic on referral processes to a regional Occupational lung disease service – a single centre experience. (11th November 2022) - Ho, CK; Macfarlane, J; Tedd, H; Dilks, C
Abstract : Introduction: The Covid-19 pandemic has dramatically impacted on both emergency and elective healthcare. Routine lung function testing in the community and the workplace virtually stopped overnight, working environments changed, with home working and the nationwide 'furlough' scheme. Little is understood about how these factors have impacted on regional Occupational lung disease (OLD) services. Objective: To investigate if and how the Covid-19 pandemic has affected the referrals into a regional OLD clinic, by comparing pre pandemic (2019) and peri/post pandemic (2021) referrals. Methods: All new OLD referrals seen in 2019 and 2021 were included for analysis. Information on primary diagnoses and routes of referrals was gathered from clinic letters. Results: The total numbers of new referrals seen in 2019 and 2021 were 116 and 68 respectively. The commonest route of referral in 2019 was primary care and regional Interstitial Lung Disease (ILD) service in 2021. There was a substantial drop in patients referred from primary care (n=39, 34% in 2019 vs n=15, 22% in 2021) and workplace based occupational healthcare providers (n=21, 18% in 2019 vs n= 2, 3% in 2021). Patients with underlying ILD (most commonly asbestosis or idiopathic pulmonary fibrosis) accounted for the commonest diagnosis (n=52, 45% in 2019 vs n=41, 60% in 2021). The number of patients diagnosed with airway diseases, including occupational asthma, halved (n=38, 33% in 2019 vs n=19, 28% in 2021). Conclusion: During the Covid-19 pandemic, we identified a 40% drop in referrals between 2019 and 2021, including a substantial reduction in referrals from workplace based occupational healthcare providers and primary care. Similarly, we diagnosed half as many patients with airway diseases, including occupational asthma. Our observations are in line with the experience of other regional OLD services, and are most likely explained by: workers being furloughed or working from home, thereby removing harmful workplace exposures; or the cessation of routine workplace surveillance and community spirometry. British Thoracic Society has recently published a clinical statement on occupational asthma which reiterates that delayed diagnosis of occupational asthma has a poorer prognosis, so it is crucial that we ensure patients with suspected occupational asthma are referred early.